3D Printing Using Ti-Al Nanopowders: Mechanisms of Structure Formation - Vladimir Promakhov; Alexey Matveev; Artem Babaev; Nikita Schulz; Nikita Toropkov; Alexander Vorozhtsov; Marat Lerner (Metals, 2022)
In the presented research work, 3D materials were fabricated by additive moulding by means of extrusion of a mixture of high filled polymers and nanopowders of Ti-Al intermetallides with subsequent sintering at 1100 ± 20 °C, 1200 ± 20 °C and 1250 ± 20 °C (MEAM-HP process). Nanopowders of Ti-Al intermetallides were obtained by the electrical explosion of intertwined aluminium and titanium wires. It was found that the structure of the materials comprises an AlTi matrix with Ti2AlN MAX-phase particles distributed within it, surrounded by a composite layer of Ti3Al-Ti2AlN. Sintering temperature increases led to changes in the concentration of TiAl, Ti3Al and Ti2AlN phases in the samples. Besides that, aluminium oxide particles were discovered in the structure of the materials. It was found that as the sintering temperature was increased from 1100 ± 20 °C to 1250 ± 20 °C, the average microhardness of the samples increased from 193 to 690 HV0.1.